Meta-Communicative Expressions and Situational Variation of Stance Marking: I say and I tell (you) in Early Modern English Dialogues - Landert, Daniela (Nordic Journal of English Studies, 2017)
In this study, I compare the functions of I say and I tell (you) in the different text types in A Corpus of English Dialogues 1560–1760 (CED). The text types differ with respect to a number of parameters, such as the authenticity of the dialogue, the stability of the participant roles, the formality of the setting, and the dominant verbal activities. I show that the two expressions are used with a range of different functions, most of which express the speaker’s stance, and I argue that the differences in function are related to differences in the communicative setting and the roles of the participants.